Neo nolin “genre” new music - Mawan, I Gede (International journal of linguistics, literature and culture, 2021)
The development of Mandolin music today is experiencing very rapid development. We can see this in the presence of various artistic creativities that are present in the midst of society. The presence of artistic creativity is due to the opening of wide creative spaces for the younger generation who love traditional music. Various types of new repertoires have appeared to color the development of Mandolin music today as a result of this freedom of space to create the repertoire work and the musical instruments. This has resulted in the emergence of many new musical genres in the community. The main problems discussed in this study include: What is the form of renewal carried out in Mandolin music? What are instrument development, repertoire, and presentation system? This research aims to identify, describe, and analyze the form of Mandolin music from classical to its development. Data were analyzed using interpretive qualitative methods, and the results of the analysis were presented informally in narrative form. The results of this study indicate that Neo Nolin is a renewal of the existing Mandooin music, reconstructed to present a new atmosphere, form, and presentation system that is more aesthetically attractive.